Influence of social networks and environmental factors on older adults’ regular walking - Kim, Hwajun; Ko, Young (Frontiers in Public Health, 2025)
IntroductionFew studies have confirmed the influence of social networks and environmental factors on the regular walking of older adults in the community. This study aimed to identify factors influencing regular walking, focusing on social networks and the walkability of the neighborhood environment.MethodsThis study is a secondary analysis of a cross-sectional survey conducted with 840 community-dwelling older adults. Multiple logistic regressions were performed to determine the factors influencing regular walking.ResultsOlder women are 1.58 times more likely to walk regularly than men. For older men, the likelihood of regular walking increased 1.56 times as their frequency of contact with friends and neighbors increased. For older women, the probability of regular walking increased by 1.39 times when street connectivity improved. Habitual walking probabilities were lowered by 1.45 times for older women when the terrain was hilly.DiscussionHealth care providers should consider their social networks and environmental factors while developing strategies to promote regular walking in older adults.